CHARACTERIZATION OF LIGHTWEIGHT LIME MORTARS CONTAINING BRICK WASTE POWDER - Martin Vyšvařil; Tomáš Žižlavský; Patrik Bayer; Pavla Rovnaníková (Acta Polytechnica CTU Proceedings)
This work deals with the effects of an expanded perlite (EP) on the hardened properties of air lime mortars with a 50% brick waste powder content. The influence of different substitution of quartz sand by EP is also monitored here. A relationship between EP content and physical-mechanical properties of mortar (flexural and compressive strength, pore system) and mortar frost resistance has been found. Very good contact between the binder matrix and EP surface was observed in microstructural images of mortars that conclusively exhibits the formation of products by pozzolanic reaction on the surface of EP. This work could be helpful for the establishment of the essential proportions of EP and quartz sand to be used in air lime mortars designed for restoration works.